Training Need Assessment of Board of Directors of Farmer Producer Companies: An Application of Borich’s Model - Himadri Roy,; Basavaprabhu Jirli, Saikat Maji, (Indian Journal of Extension Education, 2022)
In India, small and marginal farmers face numerous technological and institutional issues to realize the actual worth of their farm produce. To overcome such vagaries of agriculture, the collectivization of agri-producers into farmer producer companies has emerged as a potential approach to boost the bargaining power and scaling up the production process. The prime operational issues in FPCs are the result of both the limited resource availability and the capacity deficit of the governing members. Thus, a descriptive study was conducted during 2021-2022 to probe into the training needs of the Board of Directors (BoD) of FPCs in Eastern Uttar Pradesh. Three FPCs were randomly selected from each of the 28 districts of eastern Uttar Pradesh, and from each selected FPC, one BoD was interviewed. Based on Borich’s need assessment model the perceived level of training need was accessed for the respondents in 34 different core training areas under 7 major domains with a standardized interview schedule. The training needs were analyzed and ranked based on the mean weighted discrepancy scores. Some of the most prioritized training areas included strategic planning for FPC activities, preparation of business plan, and financial aspects of business plan etc.